1999
DOI: 10.1021/ma991374j
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Aggregates in Partially Zn-Neutralized Poly(ethylene-ran-methacrylic acid) Ionomers:  Shape, Size, and Size Distribution

Abstract: The ionic aggregates in a series of partially Zn-neutralized poly(ethylene-ran-methacrylic acid) ionomers have been imaged using scanning transmission electron microscopy. The profound advantage of this technique is the direct interpretation of the images for the shape, size, and size distribution of the ionic aggregates. Using tilt series and aspect ratios, the aggregates at all neutralization levels (17−78%) and both as-extruded and recrystallized were found to be spherical. The diameter of the Zn-rich aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 11 publications
8
69
0
Order By: Relevance
“…As mentioned above, the combined SAXS profile of pristine SPEEK membrane showed a broad hump, similar to the so-called "ionomer peak" identified in a wide range of ionomer materials, including Nafion, 49 poly(ethylene-ran-methacrylic acid)-based 50 and poly(ethylene-co-acrylic acid) 51 based ionomers. Despite a large library of related work, a universally accepted morphological model for the solid-state structure of these ionomers has yet to emerge.…”
Section: Resultssupporting
confidence: 57%
“…As mentioned above, the combined SAXS profile of pristine SPEEK membrane showed a broad hump, similar to the so-called "ionomer peak" identified in a wide range of ionomer materials, including Nafion, 49 poly(ethylene-ran-methacrylic acid)-based 50 and poly(ethylene-co-acrylic acid) 51 based ionomers. Despite a large library of related work, a universally accepted morphological model for the solid-state structure of these ionomers has yet to emerge.…”
Section: Resultssupporting
confidence: 57%
“…No lines have been seen in any ionomer micrograph to this reviewer's knowledge. Further, in two studies, [120,121] samples were tilted slightly to determine if the diameter or aspect ratio changed with tilt angle, and no changes were seen. With likely diameter/thickness ratio between 3 and 5 for a reasonable planar circular structure, it is not clear whether tilting experiments definitely rule out circular planar aggregates; but certainly, the lack of change with tilting does make circular aggregates unlikely.…”
Section: Ionic Aggregates: Nanometer Length Scalementioning
confidence: 99%
“…ZnEMAA [121] Spheres, $2.1 nm Extrusion. Size almost independent of neutralization level, polydispersity index less than 1.5.…”
Section: Compression Moldingmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous high-voltage transmission electron microscopy (TEM) study of solution-cast thin films of Zn-SPS 21 showed promise in this regard, although the effect of solution casting on ionomer morphology has since been shown to depend on solution composition. 22 Recently, Winey and colleagues 23,24 imaged the ionic aggregates of semicrystalline poly(ethylene-comethacrylic acid) random ionomers using STEM equipped with a field emission electron gun (FEG). The bulk morphologies of these ionomers were maintained using cryo-ultramicrotomy for sample preparation.…”
Section: Introductionmentioning
confidence: 99%